Continents and supercontinents - Rogers, John J. W. (John James William), 1930-2015 (OUP E-Books., 2004)
Surveys the origin of continents, and the accretion and breakup of supercontinents through earth history. This book also shows how these processes affected the composition of seawater, climate, and the evolution of life.